Developing a Database of Structural Racism–Related State Laws for Health Equity Research and Practice in the United States. (July 2021) - Agénor, Madina; Perkins, Carly; Stamoulis, Catherine; Hall, Rahsaan D.; Samnaliev, Mihail; Berland, Stephanie; Bryn Austin, S.
Objectives: Although US state laws shape population health and health equity, few studies have examined how state laws affect the health of marginalized racial/ethnic groups (eg, Black, Indigenous, and Latinx populations) and racial/ethnic health inequities. A team of public health researchers and legal scholars with expertise in racial equity used systematic policy surveillance methods to develop a comprehensive database of state laws that are explicitly or implicitly related to structural racism, with the goal of evaluating their effect on health outcomes among marginalized racial/ethnic groups. Methods: Legal scholars used primary and secondary sources to identify state laws related to structural racism pertaining to 10 legal domains and developed a coding scheme that assigned a numeric code representing a mutually exclusive category for each salient feature of each law using a subset of randomly selected states. Legal scholars systematically applied this coding scheme to laws in all 50 US states and the District of Columbia from 2010 through 2013. Results: We identified 843 state laws linked to structural racism. Most states had in place laws that disproportionately discriminate against marginalized racial/ethnic groups and had not enacted laws that prevent the unjust treatment of individuals from marginalized racial/ethnic populations from 2010 to 2013. Conclusions: By providing comprehensive, detailed data on structural racism–related state laws in all 50 states and the District of Columbia over time, our database will provide public health researchers, social scientists, policy makers, and advocates with rigorous evidence to assess states' racial equity climates and evaluate and address their effect on racial/ethnic health inequities in the United States.